RANCANG BANGUN ALAT PENGIRIS PEMPEK MENJADI KEMPLANG - Sabina Sabina; Suwito Suwito; Yang Fitri Arriyani; Subkhan Subkhan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
This final project makes pempek which is the basic material for making kemplang as the object of research. Based on the results of a survey conducted in Kampung Pasir until now pempek slicing is still done manually using a kitchen knife which requires slicing time of about 1 hour for slices weighing ±4.3 kg or 1 minute for slices of 71.7 grams. The purpose of this final project is to design a pempek slicer as many as 4 butts measuring 25 cm long with a diameter of 4 cm and a thickness of 2-3 mm that can be sliced in one slicing process. The design of the pempek slicer into kemplang refers to the VDI 2222 design method. From the experiment, it was found that the pempek slices were uniform in thickness and the tool could slice the pempek within 10 kg/hour.